Effect of Branding and Familiarity of Soy Sauces on Valence and Arousal as Determined by Facial Expressions, Physiological Measures, Emojis, and Ratings - de Wijk, Rene A.; Ushiama, Shota; Ummels, Meeke J.; Zimmerman, Patrick H.; Kaneko, Daisuke; Vingerhoeds, Monique H. (Frontiers in Neuroergonomics, 2021)
Food experiences can be summarized along two main dimensions: valence and arousal, which can be measured explicitly with subjective ratings or implicitly with physiological and behavioural measures. Food experiences are not only driven by the food’s intrinsic properties, such as its taste, texture, and aroma, but also by extrinsic properties such as brand information and the consumers’ previous experiences with the foods. In this study, valence and arousal to intrinsic and extrinsic properties of soy sauce were measured in consumers that varied in their previous experience with soy sauce, using a combination of explicit (scores and emojis), implicit (heart rate frequency and skin conductance), and behavioural measures (facial expressions). Forty participants, high- and low-frequency users, were presented with samples of rice and three commercial soy sauces without and with brand information that either matched or non-matched the taste of the soy sauce. In general, skin conductance and facial expressions showed relatively low arousal during exposure to the brand name, increased arousal in anticipation of the taste, and again lowest arousal during tasting. Heart rate frequency was lowest during exposure to the brand name, increased during anticipation, and increased further during tasting (probably resulting from the motor activity during chewing). Furthermore, the results showed that explicit liking and arousal scores were primarily affected by the taste of the specific soy sauce and by the participants’ previous experience with soy sauces. These scores were not affected by branding information. In contrast, facial expressions, physiological skin conductance (level and response), and heart rate frequency were primarily affected by 1) the participants’ level of experience with soy sauce, 2) whether or not branding information was provided, and 3) whether or not the branding information matched with the taste. In conclusion, this study suggests that liking scores may be most sensitive to the food’s intrinsic taste properties, whereas implicit measures may be most sensitive to extrinsic properties such as brand information. Both explicit and implicit measures were affected by the consumers’ previous food experiences.